Paradigma Konseling Dan Psikoterapi:Tinjauan Literatur Sistematis Atas Landasan Teoretis,Pendekatan, Dan Teknik Intervensi - Donal, Donal; Karneli, Yeni; Ardi, Zadrian; Hariko, Rezki (At-Taujih : Bimbingan dan Konseling Islam, 2026)
Counseling and psychotherapy have developed into disciplines characterized by extraordinary paradigmatic diversity, yet comprehensive systematic reviews integrating recent theoretical developments across paradigms particularly from non-Western perspectives remain limited. Objective: This article aims to map and classify major counseling and psychotherapy paradigms, synthesize empirical evidence on therapeutic effectiveness and change mechanisms, and analyze the applicability of Western-developed frameworks in Indonesian and Southeast Asian contexts. Method: A Systematic Literature Review (SLR) following PRISMA 2020 guidelines was conducted through structured searches across four databases: Scopus, Web of Science, PubMed, and Google Scholar (January 2026). Boolean keyword strings combined terms for psychotherapy paradigms, therapeutic alliance, evidence-based practice, and multicultural competence. From 4,847 initial records, 49 articles met inclusion criteria following deduplication, independent screening (Cohen's κ = 0.84), and JBI Critical Appraisal (threshold ≥ 50%). Results: Three principal findings emerged: (1) eight major paradigms were identified and classified psychoanalytic/psychodynamic, humanistic-existential, cognitive-behavioral, contextual-behavioral, systemic-family, integrative/eclectic, multicultural-ecological, and neurobiological; (2) common therapeutic factors, particularly therapeutic alliance (r = 0.28–0.30), account for greater outcome variance than specific techniques; and (3) none of the 49 included studies originated from Indonesia, and only four from Asia, confirming a critical research gap. Conclusion: No single paradigm demonstrated universal superiority. The novelty of this review lies in explicitly connecting the WEIRD critique to Indonesian counseling education and proposing a culturally-adapted integrative framework as a priority for future empirical development in the region. Keywords: psychotherapy paradigms; therapeutic alliance; multicultural counseling; Indonesia; non-Western psychotherapy